You are on page 1of 7

Boolean Algebra

2/23/01

Assume that a Boolean Algebra B has elements that take one of two values 0 or 1.

Axioms - Rules of Boolean Algebra. 1a 1b 2a 2b 3a 3b 4a 4b 00=0 1+1=1 11=1 0+0=0 01=10=0 1+0=0+1=1 If x=0, then x'=1 If x=1, then x'=0

Single variable theorems from axioms: 5a 5b 6a 6b 7a 7b 8a 8b 9 x0=0 x+1=1 x1=x x+0=x xx=x x+x=x x x' = 0 x + x' = 1 x'' = x Prove by induction substituting x=0 and x=1 and use the axioms.

Duality Given a logic expression, its dual is obtained by replacing all + operations with operations and vice versa, and by replacing all 0s with 1s and vice versa. The dual of any true statement is also a true statement. Pairs of single variable theorems are duals. Two and three variable properties: 10a 10b 11a 11b 12a 12b 13a 13b 14a 14b 15a 15b 16a 16b xy=yx x+y=y+x x (y z) = (x y) z x + (y + z) = (x + y) + z x (y + z) = x y + x z x + y z = (x + y) (x + z) x+xy=x x (x + y) = x x y + x y' = x (x + y) (x + y') = x (x y)' = x' + y' (x + y)' = x' y' x + x' y = x + y x (x' + y) = x + y DeMorgans Theorem Commutative (10a's dual) Associative

Distributive

Absorption

Can prove by induction or by algebraic manipulation.

Proof of DeMorgans Theorem 15b: (x + y) = x' y'


xy 00 01 10 11 LHS x+y (x+y)' 0 1 1 0 1 0 1 0 x' 1 1 0 0 RHS y' x'y' 1 1 0 0 1 0 0 0

Problem 2.1

Prove x + yz = (x + y)(x + z)

x + yz = (x + y)(x + z) = xx + xz + xy + yz = x + xz + xy + yz = x (1 + z + y) + yz = x (1) + yz = x + yz Problem 2.2 Prove (x + y) (x + y') = x

x = (x + y) (x + y') = xx + xy + xy' + yy' = x + xy + xy' + yy' = x + xy + xy' + 0 = x (1 + y + y') = x (1) =x Truth tables or algebraic manipulation can be used to prove two expressions are equivalent. Algebraic manipulation can also be used to reduce an expression (or circuit).

Simplifican of Boolean Functions


xy 00 01 10 11 f 1 1 1 0

x y f

f = x'y' + x'y + xy' = x'(y' + y) + xy' = x'(1) + xy' = x' + xy'

f x

F = yz + xyz' + xyz + xy'z' + xy'z


y z x y z' x y z x y' z' x y' z F

F = yz + xyz' + xyz + xy'z' + xy'z = yz + x(yz' + yz + y'z' + y'z) = yz + x(y(z + z') + y'(z' + z)) = yz + x(y(1) + y'(1)) = yz + x(y + y') = yz + x(1) = yz + x

y z x

F(x,y,z) = (1, 2, 3, 6) = x'y'z + x'yz' + x'yz + xyz' = x'y'z + x'yz + yz'(x'+x) = x'y'z + x'yz + yz' = x'z(y'+y) + yz' = x'z(1) + yz' = x'z + yz'

F(x,y,z) = (1, 5, 6) = x'y'z + xy'z + xyz' = y'z(x'+x) + xyz' = y'z + xyz'

Venn Diagrams:

x + y

(x + y)'

x z

x z

y + x

You might also like